ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PENGELOLAAN DANA DESA DI KECAMATAN PINTU RIME GAYO - Silviyana Warmansyah; Taufik; Angga Syahputra (J-ISCAN: Journal of Islamic Accounting Research, 2022)
The purpose of this study is to determine the effect of work performance, skills, attitudes and leadership on the performance of village fund management in the village of Pintu Rime Gayo District. The type of research that used is quantitative research. Data source that used in this study is primary data obtained by using a questionnaire and measured using a Likert Scale. While the data analysis method used used in this study is a method of multiple linear regression analysis. The results of the study show that work performance, behavioral and leadership skills have a significant effect on the performance of village fund management. It can be observed from the t test that has a tcount value of 4.491 using a sig.t of 0.000 <0.05 so that the decision making Ho is rejected and Ha is accepted, then the psychological factor (X4) has a significant effect on the Performance of Village Fund Management in Pintu Rime Gayo District. The coefficient of determination (R2) with a value of 63, 3 % which shows that the influence of Variables (Factors of Job Performance, Skills, Behavior) and Leadership) jointly own influence of 63.3 % of the Village Fund Management Performance While the remaining 36.7% is determined by other factors outside of this study.